PERAN KOMUNIKASI ORANG TUA DI KELAS V SDN 1 KAPRINGAN KECAMATAN KRANGKENG KABUPATEN INDRAMAYU (Universitas Negeri Semarang, 2021)
Family involvelment in leveraging abilities and child social behaviors is urgently needed. The role of a parent in particular is significant, parents must nurture and educate their children in order to socialize and communicate well. Communication between parent and child becomes according to the pattern set by the parent. Parents not only deliver by word but also set a fine example in conduct. The purpose of this study is to know the role of parent communication with child. In this study researchers use descriptive qualitative research, which takes location at SDN 1 Kapringan Kecamatan Krangkeng Kabupaten Indramayu. That data source used is a primary and secondary source of data. The techniques used in data collection are interviews, observation, and documentation. As for the role of parent communication with child, intimacy, agreement, precision of response, and appropriate tone of voice. Based on deduced analysis and understood thet the role of communication between parents and children is quite good. This can be seen from interviews and observation that been well realized by parents at SDN 1 Kapringan Kecamatan Krangkeng Kabupaten Indramayu.